2015
DOI: 10.18632/oncotarget.6081
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated kinase group II small compound inhibitor GNE-2861 perturbs estrogen receptor alpha signaling and restores tamoxifen-sensitivity in breast cancer cells

Abstract: Estrogen receptor alpha (ERα) is highly expressed in most breast cancers. Consequently, ERα modulators, such as tamoxifen, are successful in breast cancer treatment, although tamoxifen resistance is commonly observed. While tamoxifen resistance may be caused by altered ERα signaling, the molecular mechanisms regulating ERα signaling and tamoxifen resistance are not entirely clear. Here, we found that PAK4 expression was consistently correlated to poor patient outcome in endocrine treated and tamoxifen-only tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 56 publications
(89 reference statements)
0
55
0
Order By: Relevance
“…PAK4 is involved in a variety of cytoskeletal regulation such as promoting filopodia formation, dissolution of stress fibers, controlling actin polymerization and depolymerization as well as focal adhesion turnover [19][20][21][22][23][24][25] . Consistently, PAK4 overexpression is correlated with poor patient outcome in breast cancer patients, and its overexpression in breast cancer cell lines was shown to increase cell survival, anchorage-independent growth, cell migration and invasion [26][27][28][29][30] . PAK4 also plays an essential role during embryonic development, as complete depletion of PAK4 in mice caused embryonic lethality with severe defects in the heart, brain, and vasculature of the animals; however, its role in mammary gland development has not been investigated [31][32][33] .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…PAK4 is involved in a variety of cytoskeletal regulation such as promoting filopodia formation, dissolution of stress fibers, controlling actin polymerization and depolymerization as well as focal adhesion turnover [19][20][21][22][23][24][25] . Consistently, PAK4 overexpression is correlated with poor patient outcome in breast cancer patients, and its overexpression in breast cancer cell lines was shown to increase cell survival, anchorage-independent growth, cell migration and invasion [26][27][28][29][30] . PAK4 also plays an essential role during embryonic development, as complete depletion of PAK4 in mice caused embryonic lethality with severe defects in the heart, brain, and vasculature of the animals; however, its role in mammary gland development has not been investigated [31][32][33] .…”
Section: Introductionmentioning
confidence: 74%
“…Considering the known role of PAK4 in cell proliferation and invasion 26,37,38 , we next sought to determine the status of cell proliferation and expression of known markers for invasion within the mammary duct in virgin week 4 mice, a time point where the mammary epithelium is highly proliferative. To quantify cell proliferation within the duct, we labeled tissues for Ki67 and consistent with our previous results, lack of Pak4 did not alter cell proliferation in PAK4 MEp-/mice ( Fig.…”
Section: Loss Of Pak4 Does Not Alter Cell Proliferation or Invasion Mmentioning
confidence: 99%
“…An oestrogen receptor (ER) alpha ChIP-seq in MCF7 cells (Zhuang et al , 2015) comparison to the ENCODE TFBS dataset by sub-selecting ENCODE ER ChIP-seq experiments revealed that the binding pattern of ERα in MCF7 cells was more similar to its binding pattern in T-47D cells than in ECC-1 cells (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…These ERα mutant forms recruit the co‐activators in the absence of oestrogen, while the affinity for ERα antagonists is also decreased . ERα protein activity is also regulated by various post‐translational modifications, such as phosphorylation and ubiquitination . Several studies have shown that certain modifications at the ERα hinge domain enhance ERα transcriptional activity and confer tamoxifen resistance .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Several studies have shown that certain modifications at the ERα hinge domain enhance ERα transcriptional activity and confer tamoxifen resistance. 7,8 In addition to the active biological events in ERα signalling, a number of signalling pathways crosstalk with ERα via several effects. For example, numerous growth factor signalling kinases regulate ERα phosphorylation, including MAPK, RAS, AKT and PKA, [9][10][11] which subsequently enhance ERα stability or/and transcriptional activity and renders cells less sensitive to tamoxifen.…”
Section: Introductionmentioning
confidence: 99%